Microsoft SQL server 2014 query tuning & optimization - Nevarez, Benjamin (McGraw-Hill Education, 2015)
This book describes the inner workings of the query processor so you can write better queries and provide the query processor with the quality information it needs to produce efficient execution plans. Topics include: understanding how the query optimizer works; troubleshooting queries using extended events, SQL trace, dynamic management views (DMVs), the data collector, and other tools; working with query operators for data access, joins, aggregations, parallelism, and updates; speeding up queries and improving application performance; understanding statistics and how to detect and fix cardinality estimation errors; maximizing OLTP query performance using In-Memory OLTP (Hekaton) features, including memory-optimized tables and natively compiled stored procedures; monitoring and promoting plan caching and reuse; improving the performance of data warehouse queries; and handling query processor limitations with hints and other methods. --